Emerging Body Augmentation Trends on the Mental Health and Behaviours of Female Undergraduates in Lagos State-Owned Tertiary Institutions - Ogunbamowo, Waliu Babatunde; OLADIPUPO , Basirat Olushola; Daniel Oluwatobi Oshon (COMPETITIVE: Journal of Education, 2025)
This study investigated the Emerging body augmentation trends on the mental health and behaviors of female undergraduates in Lagos State-owned tertiary institutions. Two research questions and two hypotheses were formulated for this study. The descriptive survey research design was adopted in the study. The population of the study consisted of all female undergraduates in Lagos State-owned Tertiary Institutions and the Lagos State-owned Tertiary Institutions are Lagos State University, Lagos State University of Education, Lagos State University of Technology, Lagos State College of Nursing and Lagos College of Health Technology. Multistage sampling technique was adopted. Purposive Sampling Technique was used to select three Lagos State-owned University because of their predominant nature of student’s body images practices.  Two hundred (200) female undergraduates were selected from faculties/colleges in Lagos State-owned Tertiary Institutions using simple random sampling technique. Therefore, a total of 600 respondents were used for the study. The research instrument for this study was a self-developed questionnaire titled: Body Augmentation and Mental Health Questionnaire (BAMHQ). The research instrument was carefully designed to accommodate the major variables in the study. The instrument adopted a four (4) point Likert modified scale ranging from Strongly Agree (SA), Agree (A), Disagree (D) and strongly Disagree (SD). The data collected were analyzed using description statistics of frequency count and percentage for demographic data while inferential statistic of Pearson Product Moment Correlation Coefficient was used to test the stated hypothesis at 0.05 level of significance. The findings of the study showed that a significant relationships exist between roles of media representation and societal pressure that influence females decision to undergo body augmentation tends on the health of Undergraduates in Lagos State-owned Institutions; that, a significant relationship exist between psychological effects of undergoing body augmentation tends on the mental health and behavior of female undergraduates of Lagos state-owned Institutions and that a significant relationship existed between potential consequences of undergoing body augmentation tends and the mental health and behaviors of female undergraduates in Lagos state-owned Institutions. The study recommends that Lagos State-owned Institutions should considered integrating body image and mental health topics into the teaching curriculum, especially in health and psychology courses which will help students develop critical understanding of body image issues and promote self-acceptance.